Family caregiving across the lifespan - Kahana, Eva.; Biegel, David E.; Wykle, May L.; Sage eBooks; Center for Practice Innovations; Mandel School of Applied Social Sciences (Case Western Reserve University) (Thousand Oaks, Calif. ; London : SAGE, 1994)
Examining caregiving issues from a multigenerational, family life cycle perspective, this volume deals with the broad spectrum of chronic illnesses that necessitate family caregiving throughout the lifespan and discusses responses to these challenges by both caregiving families and caregiving systems.
"Published in cooperation with the Center for Practice Innovations, Mandel School of Applied Social Sciences, Case Western Reserve University."
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chronically ill -- Care; Caregivers; Electronic books